Flexible vinyl chloride-vinyl acetate-acrylic waterproof latex powder and preparation method thereof
By using vinyl chloride-vinyl acetate-acrylic acid terpolymer emulsion in latex powder, the existing latex powder has solved the shortcomings in waterproofing performance and durability, and a flexible chloroacetate waterproof latex with excellent comprehensive performance has been prepared. Powder, suitable for construction projects, improves waterproofing and construction performance, while reducing costs.
Patent Information
- Application Number
- CN202411419293.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-14
AI Technical Summary
The existing redispersible latex powder has shortcomings in waterproofing, water resistance, weather resistance, flexibility and bonding properties, and it is difficult to meet the high requirements for comprehensive performance of building materials.
Using vinyl chloride-vinyl acetate-acrylic acid terpolymer emulsion, polyvinyl alcohol aqueous solution, organosiloxane dispersion, silicone powder waterproofing agent, anti-caking agent and inorganic filler, the specific composition ratio and preparation method are used to prepare Flexible chloroacetate waterproof latex powder with excellent comprehensive performance.
It significantly improves the waterproof performance and durability of latex powder, optimizes particle size distribution and dispersion, prevents clumping, improves construction performance, and reduces costs, and is suitable for waterproof applications in construction projects.
Smart Images

Figure BDA0005080310310000061 
Figure BDA0005080310310000071 
Figure BDA0005080310310000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of redispersible latex powder, and in particular to a flexible chloroacetic acid acrylate waterproof latex powder and a preparation method thereof. Background Art
[0002] In the recent redispersible latex powder market, latex powder with waterproof properties can be divided into three categories according to its monomer composition. The first category is a binary or ternary copolymer composed of vinyl acetate as the main monomer and ethylene or other materials; the second category is a binary or ternary copolymer composed of styrene as the main monomer and acrylic acid or butadiene; the third category is a binary or ternary copolymer composed of vinyl chloride as the main monomer and ethylene or other monomers. However, no matter which base material is used, if you want to give the product good waterproof properties, you usually need to add a specific hydrophobic additive.
[0003] Although the existing redispersible latex powder products on the market meet the waterproofing needs to a certain extent, they often have some limitations. For example, although the latex powder with vinyl acetate as the main monomer has good bonding properties, its water resistance and weather resistance are poor; although the latex powder with styrene as the main monomer has good water resistance and weather resistance, its flexibility is insufficient; and although the latex powder with vinyl chloride as the main monomer has good chemical resistance and heat resistance, its bonding properties and flexibility are poor.
[0004] Therefore, the main purpose of the present invention is to invent a flexible chloroacetic acid acrylate waterproof latex powder with excellent comprehensive performance, which can overcome the shortcomings of the prior art and become a new choice on the market. Summary of the invention
[0005] In view of this, the present invention proposes a flexible chloroacetic acid acrylate waterproof latex powder and a preparation method thereof, aiming to provide a redispersible latex powder with excellent comprehensive properties to meet higher requirements for waterproof materials.
[0006] The present invention provides a chloroacetic acid acrylate waterproof latex powder, which is made of the following components:
[0007] Vinyl chloride-vinyl acetate-acrylic acid emulsion, polyvinyl alcohol aqueous solution, organosiloxane dispersion, organosilicon powder waterproofing agent, anti-caking agent and inorganic filler;
[0008] The preparation method of the vinyl chloride-vinyl acetate-acrylic acid emulsion comprises:
[0009] After mixing vinyl chloride, vinyl acetate and acrylic acid in a weight ratio of 1:2:1, a surfactant and an initiator are added, and the reaction is carried out at 60±2°C. The surfactant is polyvinyl alcohol and sodium dodecylbenzene sulfonate. The concentration of polyvinyl alcohol is controlled within a range of 3% to 7% of the monomer amount, and the concentration of sodium dodecylbenzene sulfonate is controlled within a range of 1% to 3% of the monomer amount.
[0010] Preferably, the solid content of the vinyl chloride-vinyl acetate-acrylic acid ternary copolymer emulsion is 40%-60%, and the Brookfield viscosity is 100-3000 mmpa·s;
[0011] And / or, the solid content of the polyvinyl alcohol is 10%-30%; the degree of polymerization is 300-1200, and the degree of alcoholysis is 85%-99%.
[0012] Preferably, the weight ratio of the vinyl chloride-vinyl acetate-acrylic acid emulsion to the polyvinyl alcohol aqueous solution is 5-10:1;
[0013] and / or, the weight ratio of the vinyl chloride-vinyl acetate-acrylic acid emulsion to the organosiloxane dispersion is 10-30:1;
[0014] and / or, the weight ratio of the vinyl chloride-vinyl acetate-acrylic acid emulsion to the organosilicon powder waterproofing agent is 100:0.1-1;
[0015] and / or, the weight ratio of the vinyl chloride-vinyl acetate-acrylic acid emulsion to the anti-caking agent is 100:2-10;
[0016] And / or, the weight ratio of the vinyl chloride-vinyl acetate-acrylic acid emulsion to the inorganic filler is 100:5-20.
[0017] Preferably, the organosiloxane is one or more of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, vinyl laurate, isooctyltriethoxysilane, dodecyltriethylsilane, hexadecyltriethoxysilane, and octadecyltriethoxysilane;
[0018] And / or, the organic silicon powder waterproofing agent is one or more of a silane water repellent, a siloxane water repellent, and a silicate water repellent;
[0019] And / or, the anti-caking agent is one or more of fumed silica, hydrophobic fumed silica, microcrystalline cellulose, white carbon black, and sodium aluminosilicate;
[0020] And / or, the inorganic filler is one or more of talc, washed kaolin, heavy calcium carbonate, activated heavy calcium carbonate, pregelatinized starch, and microcrystalline wax;
[0021] Preferably, the method for preparing the polyvinyl alcohol aqueous solution comprises:
[0022] After polyvinyl alcohol and deionized water are mixed and swelled, heating and stirring are performed to obtain the polyvinyl alcohol aqueous solution.
[0023] Preferably, the preparation method of the chloroacetic acid acrylate waterproof latex powder comprises:
[0024] Adding organosiloxane into water for dispersion, mixing with polyvinyl alcohol aqueous solution and stirring to obtain a mixed dispersion;
[0025] Add the mixed dispersion to the vinyl chloride-vinyl acetate-acrylic acid emulsion and stir evenly to obtain a spray liquid;
[0026] contacting the spray liquid with an anti-caking agent and spray-drying to obtain a powder;
[0027] The powder is mixed evenly with inorganic filler and organosilicon powder to obtain the chloroacetic acid acrylate waterproof latex powder.
[0028] Preferably, the spray liquid is contacted with an anti-caking agent and the powder is obtained after spray drying, comprising:
[0029] The spray liquid is pumped into a spray drying tower, and an anti-caking agent is sucked into the spray drying tower to contact with droplets of the spray liquid, and powder is obtained after spray drying; the powder is uniformly mixed with an inorganic filler and an organosilicon powder to obtain the chloroacetyl acrylate waterproof latex powder.
[0030] Preferably, the inlet air temperature of the spray drying tower is 80-140°C, the outlet air temperature is 60-85°C, the atomizer frequency is 280-380 Hz, and the peristaltic pump rate is 9-20 ml / min.
[0031] The present invention also provides an application of the above-mentioned chloroacetic acid acrylate waterproof latex powder, and the application comprises at least one of the following:
[0032] A1) Application in waterproofing;
[0033] A2) Application in the preparation of waterproof products.
[0034] The present invention also provides a waterproof product, comprising the above-mentioned chloroacetic acid acrylate waterproof latex powder.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. The present invention improves the waterproof performance of latex powder, making it more durable in harsh environments and effectively protecting buildings from moisture.
[0037] 2. By carefully selecting and adjusting the type and amount of organosiloxane, the particle size and distribution of latex powder are optimized, thereby improving its dispersibility and uniformity in cement mortar.
[0038] 3. The introduction of anti-caking agent effectively prevents the agglomeration of latex powder during storage and transportation, ensures the fluidity of latex powder, and thus improves construction performance.
[0039] 4. Adding inorganic fillers not only reduces costs, but also enhances the filling effect of latex powder and improves the mechanical properties and durability of mortar.
[0040] 5. By reasonably setting the air inlet temperature and air outlet temperature of the drying tower, the particle size of the latex powder is controlled, preventing the problem of excessive particle size caused by over-drying.
[0041] In summary, the present invention prepares a redispersible latex powder with excellent performance by optimizing the type and amount of organosiloxane, the type of anti-caking agent and the temperature setting of the drying tower. Its application in construction projects can significantly improve the waterproof performance and durability of mortar, and has broad application prospects. Compared with the prior art, the significant advantage of the present invention is that it significantly improves the waterproof performance and durability of latex powder, while reducing costs and improving construction performance, providing a more reliable and economical material selection for construction projects. DETAILED DESCRIPTION
[0042] The exemplary embodiments of the present disclosure will be described in more detail below. Although the exemplary embodiments of the present disclosure are shown below, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to be able to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0043] Example 1
[0044] 1. Materials
[0045] The raw materials were weighed according to the weight ratio, specifically: 2000 g of vinyl chloride-vinyl acetate-acrylic acid emulsion (viscosity 190 mPa·s, solid content 49.96%), 220 g of polyvinyl alcohol (PVA0588), 160 g of dodecyltrimethylsilane, 30 g of fumed silica, 27 g of silicone powder, and 210 g of heavy calcium carbonate.
[0046] The preparation method of vinyl chloride-vinyl acetate-acrylic acid emulsion involves the following steps: First, the ratio of each component needs to be accurately controlled, that is, the weight ratio of vinyl chloride, vinyl acetate and acrylic acid is 1:2:1. Then, a suitable initiator is selected, and ammonium persulfate (APS) is selected in this experiment. In addition, the reaction temperature needs to be maintained at 60°C. By adjusting the concentration of the surfactant polyvinyl alcohol (PVA) to 3%-7% of the monomer amount, and the concentration of sodium dodecylbenzene sulfonate (SDBS) to 1%-3% of the monomer amount, a series of experiments are carried out to determine the optimal surfactant concentration. Finally, the chloroacetate-acrylic acid emulsion is obtained.
[0047] 2. Preparation of chloroacetic acid propylene waterproof latex powder
[0048] The preparation steps of the polyvinyl alcohol aqueous solution are as follows: add 780g of deionized water to a three-necked bottle, start the stirrer, then add 220g of polyvinyl alcohol (PVA0588), and let it swell for 40 minutes; then use a water bath to heat the three-necked bottle to 87±1°C, and keep constant temperature stirring for 1 hour, and the straight polyvinyl alcohol is completely dissolved, thereby preparing a polyvinyl alcohol aqueous solution with a solid content of 21.34%. The preparation steps of the spray liquid are as follows: add 98g of deionized water to a beaker, then add 160g of dodecyltrimethylsilane, and stir for 15 minutes to form a dispersion; then add 515g of polyvinyl alcohol aqueous solution, continue stirring for 20 minutes, and obtain a mixed dispersion; then add 2000g of vinyl chloride-vinyl acetate-acrylic acid emulsion, stir for 30 minutes, and obtain a polyvinyl alcohol aqueous solution (i.e., spray liquid), whose viscosity is 245mPa·s and solid content is 42.22%.
[0049] The spray drying step is as follows: the spray liquid is pumped into the spray drying tower, and the anti-caking agent is sucked in at the same time, the feed rate of the peristaltic pump is adjusted to 12 ml per minute, the air inlet temperature of the drying tower is set to 130°C, the air outlet temperature is set to 75°C, and the atomizer frequency is set to 300Hz. The powder obtained after drying enters the storage tank for subsequent use. The material mixing step is as follows: the dried powder, inorganic filler, and silicone powder are mixed according to the weight ratio, and stirred for 15 minutes using a high-speed disperser to obtain a finished chloroacetyl acrylate waterproof latex powder.
[0050] Example 2
[0051] The preparation method is the same as that of Example 1, except that the organosiloxane is hexadecyltrimethoxysilane, and the amount used is 130 g; the anti-caking agent is hydrophobic fumed silica, and the amount used is 9 g; the inorganic filler is a mixture of talcum powder and kaolin in a mass ratio of 1:2.5, and the amount used is 200 g.
[0052] Example 3
[0053] The preparation method is the same as that in Example 1, except that the organosiloxane is dodecyltriethoxysilane, the air inlet temperature of the drying tower is set to 110° C., the air outlet temperature is 65° C., and the atomizer frequency is 350 Hz.
[0054] Comparative Example 1
[0055] The preparation method is the same as that of Example 1, except that the polymer emulsion is a vinyl acetate-ethylene polymer (viscosity 1200 mPa·s, solid content 56.72%).
[0056] Comparative Example 2
[0057] The preparation method is the same as that of Example 1, except that no organosiloxane and organosilicon powder are added.
[0058] Test Example 1
[0059] The performance test was performed on the latex powder obtained in each embodiment and the commercially available waterproof latex powder (referring to the standard GB / T29594-2013). Table 1 shows the performance test results.
[0060] Table 1
[0061]
[0062] Judging from the performance test results, all items have met the standard requirements, indicating that the method can continuously and stably produce latex powder that meets the standards.
[0063] The redispersible latex powder obtained in each example was diluted 100 times, and then ultrasonically stirred for 5 minutes before wet particle size test to check its resolubility. Table 2 shows the resolubility test results.
[0064] Table 2
[0065]
[0066] Judging from the results of wet particle size test, the produced redispersible latex powder has a slightly larger particle size than the original emulsion due to the grafting of long silicone chains on the surface of the latex particles, while the particle size distribution is basically consistent with the original emulsion, indicating that it has good re-dissolution performance and can be restored to the state of the original emulsion after dispersion in water.
[0067] The latex powder obtained in Examples 1-3 and Comparative Examples 1-2 and 20 parts of two commercially available products of the same type were stirred and mixed with 400 parts of P142.5 ordinary Portland cement, 600 parts of washed fine sand, 2 parts of million-grade cellulose, and 197 parts of water to obtain cement mortar, and then the performance test was carried out with reference to the standard JC / T984-2011. Table 3 shows the performance test results of the cement mortar.
[0068] Table 3
[0069]
[0070]
[0071] Among them, the commercial product 1 is a strong hydrophobic rubber powder produced by Wacker, and the commercial product 2 is a hydrophobic rubber powder produced by a domestic company. From the performance test, the anti-seepage pressure and water absorption rate of the mortar test blocks of the rubber powder obtained in Examples 1-3 are close to the imported products with the same function, better than the comparative examples and domestic products with the same function, and meet the standard requirements. However, the performance of comparative examples 1-2 shows that there are deficiencies in some aspects, especially the anti-seepage pressure and water absorption rate of comparative example 2 are poor, which may be related to the fact that no organosiloxane and organosilicon powder are added, resulting in its waterproof performance being inferior to other examples.
[0072] In practical applications, the latex powders of Examples 1-3 exhibit excellent waterproof properties and good bonding strength when preparing waterproof mortars, which makes them have broad application prospects in construction projects. In particular, Example 1 is particularly outstanding in terms of anti-seepage pressure and water absorption, which shows that it has stronger durability in harsh environments and can better protect buildings from moisture. In addition, although Examples 2 and 3 are slightly inferior to Example 1 in some properties, they are still better than the comparative examples and commercially available products, which shows that the performance of the latex powder can be further optimized by adjusting the type and amount of the organosiloxane, the type of the anti-caking agent, and the temperature setting of the drying tower.
[0073] Principle mechanism analysis:
[0074] Organosiloxane plays a key role in the preparation of latex powder. Its long chain structure can undergo a grafting reaction with the molecular chain in the polymer emulsion to form a surface active layer with excellent waterproof performance. This surface active layer can not only improve the dispersibility of latex powder in water, but also form a continuous waterproof film in cement mortar, thereby significantly improving the anti-seepage pressure of the mortar and reducing the water absorption rate.
[0075] Anti-caking agents, such as hydrophobic fumed silica, can effectively prevent latex powder from agglomerating during storage and transportation due to its fine particles and hydrophobicity. Its uniform dispersion in latex powder ensures the fluidity of latex powder, thereby ensuring the uniformity and construction performance of latex powder during use.
[0076] Inorganic fillers, such as a mixture of talc and kaolin, can not only reduce costs, but also improve the filling effect of latex powder and enhance the mechanical properties and durability of mortar through their fine particle size and high specific surface area.
[0077] During the drying process, the inlet and outlet temperatures of the drying tower have an important influence on the particle size and distribution of the latex powder. A higher inlet temperature helps to evaporate water quickly, while a lower outlet temperature helps to control the particle size of the latex powder and avoid excessive particle size caused by overdrying. The adjustment of the atomizer frequency affects the particle size distribution of the latex powder. The appropriate frequency can ensure that the particle size of the latex powder is uniform, thereby improving its dispersion and uniformity in the cement mortar.
[0078] In summary, by optimizing the type and dosage of organosiloxane, the type of anti-caking agent and the temperature setting of the drying tower, redispersible latex powder with excellent performance can be prepared. Its application in construction projects can significantly improve the waterproof performance and durability of mortar, and has broad application prospects.
[0079] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A chloroacetic acid acrylate waterproof latex powder, characterized in that: Made from the following ingredients: Vinyl chloride-vinyl acetate-acrylic acid emulsion, polyvinyl alcohol aqueous solution, organosiloxane dispersion, organosilicon powder waterproofing agent, anti-caking agent and inorganic filler; The preparation method of the vinyl chloride-vinyl acetate-acrylic acid emulsion comprises: After mixing vinyl chloride, vinyl acetate and acrylic acid in a weight ratio of 1:2:1, a surfactant and an initiator are added, and the reaction is carried out at 60±2°C. The surfactant is polyvinyl alcohol and sodium dodecylbenzene sulfonate. The concentration of polyvinyl alcohol is controlled within a range of 3% to 7% of the monomer amount, and the concentration of sodium dodecylbenzene sulfonate is controlled within a range of 1% to 3% of the monomer amount.
2. The chloroacetic acid acrylate waterproof latex powder according to claim 1, characterized in that: The vinyl chloride-vinyl acetate-acrylic acid ternary copolymer emulsion has a solid content of 40%-60% and a Brookfield viscosity of 100-3000 mmpa·s; And / or, the solid content of the polyvinyl alcohol is 10%-30%; the degree of polymerization is 300-1200, and the degree of alcoholysis is 85%-99%.
3. The chloroacetic acid acrylate waterproof latex powder according to claim 1, characterized in that: The weight ratio of the vinyl chloride-vinyl acetate-acrylic acid emulsion to the polyvinyl alcohol aqueous solution is 5-10:1; and / or, the weight ratio of the vinyl chloride-vinyl acetate-acrylic acid emulsion to the organosiloxane dispersion is 10-30:1; and / or, the weight ratio of the vinyl chloride-vinyl acetate-acrylic acid emulsion to the organosilicon powder waterproofing agent is 100:0.1-1; and / or, the weight ratio of the vinyl chloride-vinyl acetate-acrylic acid emulsion to the anti-caking agent is 100:2-10; And / or, the weight ratio of the vinyl chloride-vinyl acetate-acrylic acid emulsion to the inorganic filler is 100:5-20.
4. The chloroacetic acid acrylate waterproof latex powder according to claim 1, characterized in that: The organosiloxane is one or more of dodecyltrimethoxysilane, hexadecyltrimethoxysilane, octadecyltrimethoxysilane, vinyl laurate, isooctyltriethoxysilane, dodecyltriethylsilane, hexadecyltriethoxysilane, and octadecyltriethoxysilane; And / or, the organic silicon powder waterproofing agent is one or more of a silane water repellent, a siloxane water repellent, and a silicate water repellent; And / or, the anti-caking agent is one or more of fumed silica, hydrophobic fumed silica, microcrystalline cellulose, white carbon black, and sodium aluminosilicate; And / or, the inorganic filler is one or more of talc, washed kaolin, heavy calcium carbonate, activated heavy calcium carbonate, pregelatinized starch, and microcrystalline wax.
5. The chloroacetic acid acrylate waterproof latex powder according to claim 1, characterized in that: The preparation method of the polyvinyl alcohol aqueous solution comprises: After polyvinyl alcohol and deionized water are mixed and swelled, heating and stirring are performed to obtain the polyvinyl alcohol aqueous solution.
6. The chloroacetic acid acrylate waterproof latex powder according to claim 5, characterized in that: The preparation method of the chloroacetic acid propylene waterproof latex powder comprises: Adding organosiloxane into water for dispersion, mixing with polyvinyl alcohol aqueous solution and stirring to obtain a mixed dispersion; Add the mixed dispersion to the vinyl chloride-vinyl acetate-acrylic acid emulsion and stir evenly to obtain a spray liquid; contacting the spray liquid with an anti-caking agent and spray-drying to obtain a powder; The powder is evenly mixed with inorganic filler and organosilicon powder to obtain the chloroacetic acid acrylate waterproof latex powder.
7. The chloroacetic acid acrylate waterproof latex powder according to claim 6, characterized in that: The spray liquid is contacted with an anti-caking agent, and the powder is obtained after spray drying, comprising: The spray liquid is pumped into a spray drying tower, and an anti-caking agent is sucked into the spray drying tower to contact with droplets of the spray liquid, and powder is obtained after spray drying; the powder is evenly mixed with an inorganic filler and an organosilicon powder to obtain the chloroacetyl acrylate waterproof latex powder.
8. The chloroacetic acid acrylate waterproof latex powder according to claim 7, characterized in that: The inlet air temperature of the spray drying tower is 80-140°C, the outlet air temperature is 60-85°C, the atomizer frequency is 280-380Hz, and the peristaltic pump rate is 9-20ml / min.
9. An application of the chloroacetic acid acrylate waterproof latex powder according to any one of claims 1 to 8, characterized in that: The application includes at least one of the following: A1) Application in waterproofing; A2) Application in the preparation of waterproof products.
10. A waterproof product, characterized in that: The invention comprises the chloroacetic acid acrylate waterproof latex powder as described in any one of claims 1 to 8.
Citation Information
Cited By
High-strength waterproof coating based on butyronitrile rubber powder and preparation method of high-strength waterproof coating
CN120173452A